Earnings Quality Determinants: Evidence from Transportation and Logistics Companies - Trizka Alyaa Herdina; Imam Hadiwibowo; Mohammad Taufik Azis (Master of Accounting Universitas Trunojoyo Madura, 2023)
Companies with good earnings quality are companies that have stable and sustainable income. This research was conducted with the aim of testing whether there is an effect of Investment Opportunity Set, leverage, and liquidity on earnings quality. The objects used are transportation and logistics companies listed on the IDX for the 2018-2022 period as many as 31 companies. This research is a descriptive research with a quantitative approach. The sampling method used purposive sampling technique. There were 17 companies that met the sample criteria with 5 years of observation, so the total sample was 85 samples. The data used is secondary data sourced from the company's financial statements accessed through the website www.idx.co.id. The method applied is multiple linear regression analysis with the IBM SPSS Version 25 application. This research partially shows the results that Investment Opportunity Set and liquidity do not affect earnings quality, while leverage affects earnings quality. Taken together Investment Opportunity Set, leverage, and liquidity affect the quality of earnings.